Greece : Report on the Observance of Standards and Codes-Data Module-Update. (IMF Staff Country Reports; Country Report ;, 2005)
This update to the Report on the Observance of Standards and Codes (ROSC)-Data Module on Greece highlights general recommendations, consumer price index, government finance statistics, and balance-of-payment statistics. The National Statistical Service of Greece (NSSG) has been working toward publishing in 2005 detailed government finance statistics, including time series. National accounts press releases include charts and commentaries about recent developments. The NSSG is investigating whether provisional structural surveys could be used to improve the timeliness of the weight revisions.